2004
DOI: 10.1002/adma.200305756
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Protein Molecules by Size‐Selected Metal Clusters on Surfaces

Abstract: Protein immobilization by nanocluster films is a new route to stabilize individual protein molecules and complexes for single‐molecule measurements such as liquid‐phase atomic force microscopy (AFM) imaging (see Figure). The sub‐monolayer films of size‐selected Au clusters present protein binding sites of arbitrary density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 21 publications
(6 reference statements)
1
19
0
Order By: Relevance
“…Only ~50% of the biotin-binding sites on the avidin-coated beads were available for each of the enzymes. These results suggest that by considering the protein foot areas of GOx (50 nm 2 ) 26 and HRP (20 nm 2 ) 27 to be comparable to that of avidin (34 nm 2 ), 21 only one out of two biotin-binding sites of an avidin molecule (note that we assumed only two biotin-binding sites are present for one avidin molecule sitting on a bead surface, because two other binding sites are oriented toward the bead surface) is available for a biotin-GOx or biotin-HRP enzyme molecule. Thus, only one molecule of biotin-GOx or biotin-HRP can be bound to one avidin molecule.…”
Section: Preparation Of Microfluidic Reactors Packed With Enzymeimmobmentioning
confidence: 89%
“…Only ~50% of the biotin-binding sites on the avidin-coated beads were available for each of the enzymes. These results suggest that by considering the protein foot areas of GOx (50 nm 2 ) 26 and HRP (20 nm 2 ) 27 to be comparable to that of avidin (34 nm 2 ), 21 only one out of two biotin-binding sites of an avidin molecule (note that we assumed only two biotin-binding sites are present for one avidin molecule sitting on a bead surface, because two other binding sites are oriented toward the bead surface) is available for a biotin-GOx or biotin-HRP enzyme molecule. Thus, only one molecule of biotin-GOx or biotin-HRP can be bound to one avidin molecule.…”
Section: Preparation Of Microfluidic Reactors Packed With Enzymeimmobmentioning
confidence: 89%
“…Different studies showed that the change in the localized surface plasmon band is related to the aggregated size of Au NPs [19][20][21]. Typically the Au NPs can be readily modified with thiolcontaining biomolecules because the thiol group exhibits a strong interaction on the metal surface [22]. Generally, modified Au NPs aggregate when the terminal amino group of a biomolecule forms hydrogen bonding with the carboxyl group of another biomolecules on an adjacent nanoparticle [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, gold clusters form sites at which proteins or other organic molecules can be immobilized, 1,2 leading to the intriguing possibility of nanoscale biosensors. If the nanoclusters are projected towards the surface with a certain energy, then different energy deposition regimes result in different interaction processes between the cluster and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have been the subject of experimental investigation via the deposition of such size-selected clusters on surfaces experimentally. [2][3][4]6,7,9,10 Recently a wide ranging experimental study of the pinning thresholds for gold and nickel clusters has been made for N ranging from 10 to 300. Here we investigate the deposition of size-selected Au and Ni clusters using molecular dynamics computer simulations.…”
Section: Introductionmentioning
confidence: 99%